Brucite modified epoxy mortar binders: Flame retardancy, thermal and mechanical characterization. (15th September 2015) - Zhang, Yuge; Sun, Yifan; Xu, Ke; Yuan, Zuanru; Zhang, Jing; Chen, Ru; Xie, Hongfeng; Cheng, Rongshi
Highlights: Environmentally-friendly flame-retarded epoxy mortar binder (EMB) has been developed. The synthetic brucite significantly enhances the flame retardancy, thermal stability and mechanical properties of EMBs. The viscosity of brucite modified EMBs is low enough to satisfy the requirement of mortar pavement even at 60 °C. Abstract: Polymer mortar with excellent mechanical strength and durability has been widely used in road pavement and other construction industry. In this study, two kinds of brucites, synthetic and natural brucites were incorporated in the epoxy mortar binders as flame retardants. The components and morphology of the two kinds of brucites were investigated. The flame retardancy of brucite-modified epoxy mortar binders was evaluated by the horizontal burning and limiting oxygen index tests. The influence of flame retardants on the rotational viscosity, the thermal and mechanical properties of epoxy mortar binders was determined by differential scanning calorimetry, thermogravimetric analysis, and universal test machine. Furthermore, the morphology of flame retarded-epoxy mortar binders was characterized by scanning electron microscopy. The addition of brucites significantly improved the flame retardancy, thermal stability and tensile strength of epoxy mortar binders. Especially in the case of the addition of 20 wt% synthetic brucites in epoxy mortar binders, from FH-3 to FH-1 reduction in the horizontal burning classification, 5.5% improvement in limiting oxygen index, 15% increment in tensile strength were obtained.